2020
DOI: 10.1186/s11658-020-00222-z
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-637 promotes vascular smooth muscle cell proliferation and migration via regulation of insulin-like growth factor-2

Abstract: Background: Dysregulation of the proliferation and migration of vascular smooth muscle cells (VSMCs) is a crucial cause of atherosclerosis. MiR-637 exerts an antiproliferative effect on multiple human cells. Its impact on atherosclerosis remains largely unexplored. Methods: Real-time PCR was used to determine miR-637 expression in samples from atherosclerosis patients and animal models. Its expression in VSMC dysfunction models (induced by ox-LDL) was also measured. The proliferation and migration of VSMCs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Through application of the circInteractome database, miR-637 was predicted to be a target of circUSP36. In view of the inhibitory role of miR-637 in atherosclerosis [ 52 ], we selected miR-637 as a research object in subsequent explorations of the molecular mechanism. Luciferase reporter gene and RNA pull-down assays validated that miR-637 directly binds to circUSP36.…”
Section: Discussionmentioning
confidence: 99%
“…Through application of the circInteractome database, miR-637 was predicted to be a target of circUSP36. In view of the inhibitory role of miR-637 in atherosclerosis [ 52 ], we selected miR-637 as a research object in subsequent explorations of the molecular mechanism. Luciferase reporter gene and RNA pull-down assays validated that miR-637 directly binds to circUSP36.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that miR-637 was marked downregulated in 86 patients with atherosclerosis, which is a putative mechanism of CAS [ 18 ]. Downregulation of miR-637 is involved in atherosclerosis and promotes the proliferation and migration of vascular smooth muscle cells by regulating insulin-like growth factor 2 [ 36 ]. In patients with essential hypertension, miR-637 is typically reduced [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 An increasing number of studies have reported that ox-LDL exerts a promotion effect in the development of AS by stimulating the proliferation of VSMCs within the vessel wall. 21,22 Therefore, agents blocking or inhibiting proliferation and migration of VSMCs induced by ox-LDL may contribute to the identification of therapeutic strategies. Eplerenone is a newly found novel selective aldosterone receptor antagonist.…”
Section: Discussionmentioning
confidence: 99%